2010
DOI: 10.3141/2196-10
|View full text |Cite
|
Sign up to set email alerts
|

Generating Origin–Destination Matrices from Mobile Phone Trajectories

Abstract: This paper presents a method for generating origin–destination (O-D) matrices with the use of floating phone data, that is, data generated from mobile phones moving through a study area. Mobile phone signals recorded in the cellular phone network are used to derive time–space trajectories of moving mobile phone devices. The start and end points of each trajectory determine the origin and destination zone. Link counts are used to project the sample of mobile phone movements to the broader movement of cars, truc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…(Gonzalez et al 2008;Schneider et al 2013;Ratti et al 2006;Ratti et al 2007;Sevtsuk and Ratti 2010;Calabrese et al 2013;Hoteit et al 2014), origin-destination flows, e.g. (Tettamanti and Varga 2014;Wang et al 2013;Caceres et al 2012;Calabrese et al 2011;Friedrich et al 2010), and road usage patterns (Wang et al 2012). More detailed reviews of the use of cell phone data in traveler information systems and travel behavior studies can be found in (Qiu and Cheng 2007;Yue et al 2014;Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…(Gonzalez et al 2008;Schneider et al 2013;Ratti et al 2006;Ratti et al 2007;Sevtsuk and Ratti 2010;Calabrese et al 2013;Hoteit et al 2014), origin-destination flows, e.g. (Tettamanti and Varga 2014;Wang et al 2013;Caceres et al 2012;Calabrese et al 2011;Friedrich et al 2010), and road usage patterns (Wang et al 2012). More detailed reviews of the use of cell phone data in traveler information systems and travel behavior studies can be found in (Qiu and Cheng 2007;Yue et al 2014;Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, typical mobile phone data only have the location when a person exposes his or her location by using the phone. Extracting origins and destinations of each meaningful trip from mobile phone data needs extra work compared to taxi trip data but has attracted many researchers (Friedrich et al 2010, Calabrese et al 2011. It is also an open issue to define and reveal the semantics of human trajectories (Parent et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another application of probe vehicle systems was updating digital road maps, which had the advantages of low cost, short updating circle and high accuracy Vartziotis et al, 2012). Some studies have also applied probe vehicle data to estimate dynamic OD for traffic demand forecasting purpose (Baek et al, 2010;Friedrich et al, 2010). Recently, the extended floating car systems (xFCD) that were based on the floating cars equipped with extra visual cameras and on-board Electronic Control Units have appeared to be a more efficient way for traffic state estimation, the level-of-service estimation, and real-time road safety assessment, e.g., Kyamakya et al (2011), Messelodi et al (2009), Pell et al (2012 and Diaz et al (2012).…”
Section: Literature Reviewmentioning
confidence: 99%